2009
DOI: 10.1007/s10639-009-9086-z
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for electronic note taking systems: A field study of note taking in university classrooms

Abstract: Note taking is the core activity for students in a classroom. There has been a large amount of research conducted, both from industry and from academia, into facilitating the note-taking process. There is evidence that shows that note taking can be beneficial for the students' educational growth. There are also many available systems for taking notes electronically (e.g. Tablet PCs, PDAs). However, what has not been given as much attention is how these electronic devices affect (or support) the note taking tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…The researchers found that the notes taken with pen and paper and stylus and tablet were substantially alike, and did not differ in quantity, quality, or form. Other researchers reported similar findings regarding the content of stylus/tablet and pen/paper notes, but also noted that students felt that the interface of the tablets and PDAs was not as convenient or comfortable as plain pen and paper [32].…”
Section: Courtroommentioning
confidence: 57%
“…The researchers found that the notes taken with pen and paper and stylus and tablet were substantially alike, and did not differ in quantity, quality, or form. Other researchers reported similar findings regarding the content of stylus/tablet and pen/paper notes, but also noted that students felt that the interface of the tablets and PDAs was not as convenient or comfortable as plain pen and paper [32].…”
Section: Courtroommentioning
confidence: 57%
“…In the past decade many researchers advocated the use of computers (Bui et al 2013) and electronic note-taking systems (Ward and Tatsukawa 2003;Kim et al 2009) for recording and summarising important concepts in class. Bui et al (2013) did a study where they compared pen-and-paper note-taking with taking notes on the computer.…”
Section: Note-taking With An Electronic Devicementioning
confidence: 99%
“…Speed, legibility, and searchability are 3 positive attributes of digital note-taking. 8 Because of these advantages, some students may prefer digital note-taking vs traditional handwritten notes. However, changes wrought from these advances in technology are not all positive.…”
Section: Digital Note-takingmentioning
confidence: 99%
“…3,[5][6][7] Note-taking is a personalized task, and when individual differences with regard to note-taking ability also are considered, interpretation of the literature becomes even more complex. [8][9][10] In addition to these historically studied variables, emerging factors also affect student note-taking. The introduction of tablet computers, note-taking applications (apps), and other education technology in the classroom are altering the way students take notes and consume and process information during class.…”
Section: Introductionmentioning
confidence: 99%